White slavery - Saunders, J; Saunders, Julia Edwina (2000)
﻿ In this thesis, I argue the case for putting the industrial revolution back into literary accounts of the Romantic period. Writers of fiction played an important part in disseminating knowledge about the changes to technology and society, as well as helping to form the image of the newest social class: that of the industrial workers. Literature aspired to educate and integrate this class, as well as to influence the parallel process of educating the upper classes about the advent of the new manufacturing order. I have taken as the governing metaphor for industrialization that of 'white slavery', drawing the contrast to the contemporary movement to abolish black slavery. To illustrate the thesis, I have chosen six writers: three Romantic poets - Coleridge, Southey and Wordsworth - and three women educationalists - Hannah More, Maria Edgeworth and Harriet Martineau, each of whom represents a significant philosophical approach to a manufacturing society and who each made an important contribution to imaginative literature. Whilst the Romantic poets analysed industrialization as a divisive and demoralizing phenomenon and looked to the past for solutions, the educationalists responded to the challenge presented by the factory system by suggesting new visions of social relationships which bound moral and economic behaviour together. The thesis aspires to restore the voices of neglected women writers in the industrial debate with the aim of promoting a deeper understanding of the dynamics of the Romantic period and a fuller comprehension of its creative expression.